Pertimbangan Hukum Hakim dalam Memutus Perkara Sertifikat Hak Milik antara Pengadilan PTUN Pontianak dan PTTUN Jakarta - Rinda Robyatul Gayatrie (Uniku Law Review, 2024)
This study aims to explore variations in legal considerations taken by judges when handling the same case in the Pontianak PTUN Decision Number 25/G/2020/PTUN.PTK and Jakarta PTTUN Number 106/B/2021/PT.TUN.JKT. The method used in this study is normative, focusing on assessing the quality of legal norms based on the principles of justice, benefit, and legal certainty. The findings of the study indicate that differences in the resolution of this case were triggered by variations in the judges' interpretation of legal facts, especially regarding the deadline for filing a lawsuit in accordance with Government Regulation Number 24 of 1997. Pontianak PTUN rejected the lawsuit because it considered the deadline had passed, while Jakarta PTTUN overturned the decision by stating that there was an error in calculating the time. The conclusion of this study emphasizes the importance of consistency in the application of the law, in order to prevent uncertainty and provide justice for the parties involved in the case.